IFPRI-CCAFS Gender and Climate Change Survey Data: Kaffrine, Senegal - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
The IFPRI-CCAFS Gender and Climate Change Survey data were collected in four sites in Africa south of the Sahara in early 2013 as part of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) under the project "Increasing Women’s Resilience to Confront Climate Change." It aimed to enhance understanding of gendered climate change perceptions, impacts, adaptation and coping strategies, as well as the constraints to adaptation within selected CCAFS baseline sites in Kenya, Senegal, and Uganda. Specifically, the survey was designed to answer questions such as: • How do men and women perceive climate change and, particularly, the livelihood risks associated with climate change? • What are the gender disparities in access to and control over assets and how and to what degree does the disparity in assets affect how men and women experience climate shocks and change? • How and to what degree does asset disparity determine how men and women respond to climate shocks and change? • Which coping strategies and adaptation options are favored by women and men, respectively, and why? The survey collected detailed gender-disaggregated data on these issues to inform strategies to increase climate change resilience among both women and men.The gender survey contained 13 modules, posing questions at the household and individual levels. These modules are: 1) a household roster; 2) sketch of the farm (pre-populated from a previous survey—IMPACT Lite); 3) land ownership, management, and decision making; 4) decision-making authority on agricultural, livestock, and household decisions; 5) adoption and knowledge of climate-smart agriculture practices; 6) access to and use of climate and agricultural information services; 7) access to and use of credit; 8) membership in groups; 9) fuel and water use; 10) experience with climate shocks and coping strategies; 11) perception of climate change and its potential impacts; 12) identification of adaptation strategies; and 13) cognitive decision-making and personal values questions. Four sets of data are generated from the survey conducted in four sites-Nyando and Wote in Kenya, Rakai in Uganda, and Kaffrine in Senegal. This study contains data from Kaffrine.